2012
DOI: 10.5194/bg-9-2301-2012
|View full text |Cite
|
Sign up to set email alerts
|

Direct observations of diel biological CO<sub>2</sub> fixation on the Scotian Shelf, northwestern Atlantic Ocean

Abstract: Abstract. Much of the variability in the surface ocean's carbon cycle can be attributed to the availability of sunlight, triggering surface heat flux and photosynthesis, which in turn regulate the biogeochemical cycling of carbon over a wide range of time scales. The critical processes of this carbon cycle regulation, occurring at time scales of a day or less, however, have undergone few investigations, most of which have been limited to time spans of several days to months. Optical methods have helped to infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(73 reference statements)
4
9
1
Order By: Relevance
“…Coupling between autotrophs and heterotrophs is possibly driven by phytoplankton activity cycles56 and involves heterotrophic bacteria that use phytoplankton-released metabolites57, but also protist grazers5859 and even viruses58. These coupling/decoupling cycles are thought to exert diel rhythmic forcing on biogeochemical fluxes60; however, observations like ours, showing diel rhythms in open-ocean biogeochemical processes, are very scarce335761.…”
Section: Discussionmentioning
confidence: 64%
“…Coupling between autotrophs and heterotrophs is possibly driven by phytoplankton activity cycles56 and involves heterotrophic bacteria that use phytoplankton-released metabolites57, but also protist grazers5859 and even viruses58. These coupling/decoupling cycles are thought to exert diel rhythmic forcing on biogeochemical fluxes60; however, observations like ours, showing diel rhythms in open-ocean biogeochemical processes, are very scarce335761.…”
Section: Discussionmentioning
confidence: 64%
“…Assuming a DIC : O 2 ratio of 1 : 1, this term added 0.3 mmol DIC m −3 day −1 to each layer, or removed O 2 at a rate of −0.3 mmol O 2 m −3 day −1 . This chosen respiration rate is small compared to prior estimates on the nearby Scotian Shelf (Thomas et al, 2012), and lies in the low end of the range (0.02-75 mmol O 2 m −3 day −1 ) listed in a global compilation study of water-column respiration rates (Robinson and Williams, 2005) Fig. 6).…”
Section: Numerical Model Resultsmentioning
confidence: 99%
“…7(c) along with their respective error estimates. NCP values from Thomas et al (2012) are also shown for comparison. Error bars for this study represent the combination of uncertainties calculated using standard propagation of error techniques.…”
Section: Changes In Phytoplankton Carbon δC Pmentioning
confidence: 98%
“…(b) Seasonal pattern of the rate of change of phytoplankton carbon, ΔC p . (e) ΔC p and net community production (NCP) with error estimates shown for this study, andThomas et al 2012.…”
mentioning
confidence: 98%